Novel Application of Metal–Organic Frameworks as Efficient Sorbents for Solid-Phase Extraction of Chemical Warfare Agents and Related Compounds in Water Samples - Woźniak, Jakub; Popiel, Stanisław; Nawała, Jakub; Szczęśniak, Barbara; Choma, Jerzy; Zasada, Dariusz (Molecules (Basel, Switzerland), 2024)
In this work, we test metal–organic frameworks (MOFs) as sorbents in the solid-phase extraction (SPE) technique to determine chemical warfare agents (CWAs) and their related compounds in water samples. During this study, we used 13 target compounds to test the selectivity of MOFs thoroughly. Three MOFs were used: MIL-100(Fe), ZIF-8(Zn), and UiO-66(Zr). The obtained materials were characterized using FT-IR/ATR, SEM, and XRD. CWA’s and related compounds were analyzed using gas chromatography coupled with tandem mass spectrometry (GC-MS/MS). The effect of the type of elution solvent and the amount of sorbent (MOFs) in the column on the efficiency of the conducted extraction were verified. The LOD ranged from 0.04 to 7.54 ng mL−1, and the linearity range for the analytes tested extended from 0.11/22.62 (depending on the compound) to 1000 ng mL−1. It was found that MOFs showed the most excellent selectivity to compounds having aromatic rings in their structure or a “spread” spatial structure. The best recoveries were obtained for DPAA, CAP, and malathion. Environmental water samples collected from the Baltic Sea were analyzed using an optimized procedure to verify the developed method’s usefulness.